Entry strategy for investment into Vietnam : case studies from the telecommunications industry. - Pham, Uyen Nguyen. (2009)
Vietnam has made tremendous progress since its economic renovation program in 1986. Its investment climate is constantly changing. After the Eighth Party Congress held recently in June 1996, the investment situation is due to change again as the government is more selective about the types of investments it wants. Foreign companies are also more aware of the pitfalls of investing in Vietnam.